Transforming Higher Education Management through Evidence Based and Data Oriented Approaches - Cesna, Galih Putra; Agustiawan, Sonny; Panjaitan, Aropria Saulina; Purnama, Suryari; Ikhsan, Ramiro Santiago (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
Amid the rapid advancement of digital transformation, higher education institutions are increasingly required to enhance management effectiveness and decision-making quality through the adoption of data-driven innovations. The background of this study highlights the importance of employing an evidence based approach to address the complex managerial and academic challenges faced by universities. The main objective of this research is to analyze how the implementation of data-oriented approaches can drive transformation in higher education governance, particularly in improving institutional performance, administrative efficiency, and strategic planning. This study employs a mixed method approach by combining quantitative analysis of institutional data with 50 qualitative interviews involving academic leaders to explore the relationship between data utilization and institutional management outcomes. The findings reveal that universities implementing robust data governance systems and optimizing analytical tools experience significant improvements in decision-making effectiveness, resource allocation, and stakeholder engagement, resulting in more transparent and adaptive management systems. Furthermore, the study finds that the success of data-driven management is not solely determined by technological readiness but also by organizational culture, leadership commitment, and the data literacy of personnel. In conclusion, the adoption of evidence-based and data-oriented management approaches can significantly transform higher education institutions into more innovative, responsive, and accountable entities capable of adapting to global changes and challenges in the academic landscape.